High-efficiency photocatalytic hydrogen production material prepared by utilizing photo-thermal synergistic pulse type deposition method and preparation and application of high-efficiency photocatalytic hydrogen production material

Through the photothermal collaborative pulse deposition method, the problem of uneven deposition layer thickness and long time in the photodeposition method is solved, the photocatalytic performance and stability of Zn3In2S6 material are improved, and high-efficiency photocatalytic hydrogen production materials are achieved Preparation and application.

CN119114109APending Publication Date: 2024-12-13SICHUAN AGRI UNIV

Patent Information

Application Number
CN202411253517.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing photodeposition methods have problems of uneven deposition layer thickness and long deposition time, which limit the photocatalytic performance and stability of Zn3In2S6 materials.

Method used

Photothermal synergistic pulse deposition method is adopted to carry out photothermal synergistic pulse deposition reaction by circulating switch xenon light source and Vs-Zn3In2S6 and (NH4)2MoS4 mixture in alcohol solution, and directionally deposition promoter to improve the active site and light absorption of the material. scope.

Benefits of technology

It improves the photocatalytic conversion efficiency and sunlight utilization efficiency of the material, enhances the absorption capacity in visible light and near-infrared areas, simplifies the process flow, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114109A_ABST
    Figure CN119114109A_ABST
Patent Text Reader

Abstract

The method comprises the steps that Vs-Zn3In2S6, (NH4) 2MoS4 and an alcoholic solution are mixed, inert gas is introduced, the mixture is placed under a xenon lamp light source to be subjected to a photo-thermal synergistic pulse type deposition reaction, solids are centrifugally collected, washed and dried, and the high-efficiency photocatalytic hydrogen production material is obtained. And grinding to obtain the efficient photocatalytic hydrogen production material. The method solves the problems that the thickness of a deposition layer is not uniform and the deposition time is long in an existing deposition method. The co-catalyst can be directionally deposited on the surface of the semiconductor material in a short time through a photo-thermal synergistic pulse type deposition method, so that the active sites of the material are greatly improved, the reflection of light is reduced, the absorption range of the light is enhanced, and the material has very strong absorption peaks in visible light and near-infrared regions; therefore, the utilization efficiency of sunlight and the photocatalytic conversion efficiency are improved. The method is simple, environmentally friendly, free of precious metal addition and suitable for actual industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photothermal synergistic pulsed optical deposition method, and in particular to a high-efficiency photocatalytic hydrogen production material prepared by the photothermal synergistic pulsed optical deposition method, and the preparation and application of the material. Background Art

[0002] Zn m In2S 3+m (m=1-3) materials are layered semiconductor materials that have attracted attention due to their sensitivity to visible light and excellent photoelectric properties and stability. Among them, Zn3In2S6 (m=3) has been widely studied in the field of photocatalysis because it has a suitable band gap (2.5~2.8eV) for photocatalytic H2 evolution, selective oxidation of aromatic alcohols, CO2 reduction and photocatalytic N2 fixation. However, as the research gradually deepens, some limiting factors have become increasingly prominent. The low efficiency of photogenerated carrier separation and transmission, and the poor stability caused by photocorrosion have limited the development and application of Zn3In2S6.

[0003] Researchers have been conducting extensive and in-depth explorations on the above issues, including heterostructure construction, element doping, co-catalyst modification and morphology regulation, to improve the photocatalytic performance of Zn3In2S6. Among them, co-catalyst modification can significantly improve the separation efficiency of photogenerated electrons and holes, reduce their recombination rate, and thus improve the rate and efficiency of the catalytic reaction. Deposition technology is widely used because it can accurately control the distribution of catalysts on the surface of materials, improve catalytic efficiency and material stability. At present, material deposition technologies mainly include chemical vapor deposition (CVD), physical vapor deposition (PVD) and photodeposition methods. These technologies have been widely used in industry and scientific research.

[0004] However, existing chemical vapor deposition (CVD) technology has problems such as high temperature requirements, complex gas processing and difficulty in uniformity control, while physical vapor deposition (PVD) faces problems such as low deposition rate, poor film adhesion and high equipment cost. Although the photodeposition method has the potential to improve the surface properties of photocatalytic materials, its uneven deposition layer thickness, long deposition time and other issues that affect the surface structure of the material have limited its large-scale application to a certain extent. Summary of the invention

[0005] The purpose of the present invention is to provide a high-efficiency photocatalytic hydrogen production material prepared by a photothermal synergistic pulse deposition method and its preparation and application, which solves the problems of uneven deposition layer thickness and long deposition time in existing photodeposition methods, increases the active sites of the material, reduces light reflection, and enhances the light absorption range, so that the material has strong absorption peaks in the visible light and near-infrared regions, thereby improving the utilization efficiency of sunlight and the photocatalytic conversion efficiency.

[0006] In order to achieve the above object, the present invention provides a method for preparing a high-efficiency photocatalytic hydrogen production material by using a photothermal synergistic pulse deposition method, the method comprising:

[0007] Vs-Zn3In2S6 (Zn3In2S6 containing sulfur vacancies), (NH4)2MoS4 and alcohol solution were mixed, inert gas was introduced, and the mixture was placed under a xenon lamp light source for photothermal synergistic pulse deposition reaction. The solid was collected by centrifugation, washed, dried and ground to obtain the highly efficient photocatalytic hydrogen production material MoS x @Vs-Zn3In2S6; The photothermal synergistic pulse deposition reaction is carried out under the action of a cyclic switching xenon lamp light source.

[0008] The photothermal synergistic pulse deposition method of the present invention can affect the deposition performance of the co-catalyst. The use of a cyclic switching xenon lamp light source not only saves energy, but also enables the semiconductor material to be efficiently photodeposited when illuminated, so that the co-catalyst is directionally deposited on the surface of the semiconductor material, and under dark conditions, the co-catalyst deposited on the surface of the semiconductor material can be made more stable.

[0009] Preferably, the illumination intensity of the xenon lamp light source is 100 mW / cm 2 The intensity of the xenon lamp light source will affect the deposition reaction time; the xenon lamp is externally connected to a sunlight simulation filter.

[0010] Preferably, the cyclic switching xenon lamp means that the light is turned on for 10 to 30 minutes each time and the light is turned off for 1 to 5 minutes each time.

[0011] More preferably, the cyclic switching xenon lamp means that the light is turned on for 29 minutes each time and turned off for 1 minute each time. The cyclic switching time will affect the stability of photothermal deposition. Turning off the light for too long will cause the catalyst to dissolve, while turning off the light for too short will reduce the stability of the catalyst.

[0012] Preferably, the amount of Vs-Zn3In2S6 added is 100 mg, the amount of (NH4)2MoS4 added is 0.06 mmol, and the volume of the alcohol solution is 50 mL. The amount of Vs-Zn3In2S6 and (NH4)2MoS4 added will affect the activity of the photocatalyst. The addition of fixed Vs-Zn3In2S6 and too little (NH4)2MoS4 co-catalyst deposit will reduce the active sites of the photocatalyst, resulting in reduced photocatalytic efficiency. Too much co-catalyst will cover the active sites of the catalyst, resulting in reduced separation efficiency of photogenerated electrons and holes in the photocatalyst, thereby reducing the photocatalytic efficiency.

[0013] The type of co-catalyst will affect the intensity of the photocatalytic reaction. The addition of different co-catalysts will modify the oxidation or reduction ability of the semiconductor material differently.

[0014] Preferably, the alcohol solution is an ethanol solution or a methanol solution.

[0015] More preferably, the concentration of the alcohol solution is 10% v / v to 30% v / v. The concentration of the ethanol solution will affect the solubility between the photocatalyst and the co-catalyst, thereby affecting the deposition effect of the catalyst. Too high or too low a concentration is not conducive to the reaction between the photocatalyst and the co-catalyst.

[0016] Preferably, the washing is carried out with anhydrous ethanol and deionized water; the drying temperature is 60° C. and the drying time is 12 hours.

[0017] The invention provides a high-efficiency photocatalytic hydrogen production material prepared by the method described above.

[0018] The present invention provides an application of the highly efficient photocatalytic hydrogen production material as described above in hydrogen production and / or high-value conversion of biomass.

[0019] The invention discloses a highly efficient photocatalytic hydrogen production material prepared by a photothermal synergistic pulse deposition method and its preparation and application, which solves the problems of uneven deposition layer thickness and long deposition time in the existing photodeposition method, and has the following advantages:

[0020] 1. The present invention adopts a photothermal synergistic pulse deposition method, using a pulsed light source and thermal energy to assist, and can directionally deposit the catalyst on the surface of the semiconductor material in a short time, greatly improving the active sites of the material, reducing light reflection, and enhancing the light absorption range, so that the material has a strong absorption peak in the visible light and near-infrared regions, thereby improving the utilization efficiency of sunlight and its photocatalytic conversion efficiency.

[0021] 2. The method of the present invention is simple, environmentally friendly, does not require the addition of precious metals, and is suitable for actual industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the photocatalytic material prepared in Example 1.

[0023] Figure 2 The UV-visible diffuse reflectance spectra of the photocatalytic materials prepared in Example 1 and Comparative Example 1 are shown.

[0024] Figure 3 2 are XRD diagrams of the photocatalytic materials prepared in Example 1 and Comparative Example 1.

[0025] Figure 4 This is a diagram showing the hydrogen production results of the photocatalytic materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1.

[0026] Figure 5This is a diagram of the glucose conversion product of the photocatalytic material prepared in Example 1. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The sources of the reagents involved in the following examples are as follows:

[0029] The preparation method of Vs-Zn3In2S6 (Zn3In2S6 containing sulfur vacancies) material is as follows:

[0030] ZnSO with a molar ratio of 3:2:22 4. 7H2O、InCl 3. 4H2O and thioacetamide were added to 50 mL of ethylene glycol (EG), and a transparent uniform solution was obtained after stirring for 1 h. The solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor and reacted at 140-200 °C for 12 h.

[0031] Promoter MoS x Precursor (NH4)2MoS4: purchased from Aladdin (A 189030-1g, Lot#H2113178) and used directly without purification.

[0032] The xenon lamp was purchased from Beijing Zhuoli Hanguang Instrument Co., Ltd., Gloria-X500A xenon lamp.

[0033] Example 1

[0034] A method for preparing a high-efficiency photocatalytic hydrogen production material by using a photothermal synergistic pulse deposition method, the method comprising:

[0035] (1) Deposition solvent configuration

[0036] 100 mg of Vs-Zn3In2S6 and 0.06 mmol of MoS were added to the quartz reactor. x To the precursor (NH4)2MoS4, 50 mL of 20% v / v ethanol aqueous solution was added and nitrogen was introduced for 30 min.

[0037] (2) Photothermal synergistic pulsed deposition reaction

[0038] The quartz reactor after nitrogen was introduced was placed under a xenon lamp light source, and the xenon lamp light source was switched on and off cyclically to perform a photothermal synergistic pulse deposition reaction. An external AM 1.5G sunlight simulation filter was used, and the light intensity was 100mW / cm 2 The xenon lamp light source is used. Each time the light is turned on, the light is turned off for 1 minute. The cycle is repeated three times, and the total reaction time is 90 minutes. The external AM1.5G sunlight simulation filter refers to the filter of the xenon lamp, which is used to simulate sunlight.

[0039] (3) Cleaning and drying

[0040] After the reaction, the reaction solution was taken out and the solid powder was collected by centrifugation at a speed of 1000 rpm for 8 min. The sample was washed three times with anhydrous ethanol and deionized water respectively, and dried at 60 ° C for 12 h. After being fully ground (grinded by agate mortar), a uniform and efficient photocatalytic hydrogen production material (MoS) was obtained. x @Vs-Zn3In2S6), denoted as A.

[0041] like Figure 1 As shown, the SEM image of the photocatalytic material prepared in Example 1. Figure 1 It can be seen that this Example 1 successfully deposits the co-catalyst in a directionally deposited manner on the surface of the semiconductor material, and the formed nanoflower-like structure greatly increases the active sites of the material, reduces light reflection, and enhances the light absorption range, so that the material has strong absorption peaks in the visible light and near-infrared regions, thereby improving the utilization efficiency of sunlight and the photocatalytic conversion efficiency.

[0042] Example 2

[0043] A method for preparing a high-efficiency photocatalytic hydrogen production material using a photothermal synergistic pulse deposition method is basically the same as Example 1, except that:

[0044] In step (1), MoS x The amount of precursor (NH4)2MoS4 added is 0.045mmol;

[0045] The rest of the operations were the same as in Example 1 to obtain a highly efficient photocatalytic hydrogen production material (0.045MoS x @Vs-Zn3In2S6), denoted as B.

[0046] Example 3

[0047] A method for preparing a high-efficiency photocatalytic hydrogen production material using a photothermal synergistic pulse deposition method is basically the same as Example 1, except that:

[0048] In step (2), each light-on time is 19 minutes, and each light-off time is 1 minute;

[0049] The rest of the operations were the same as in Example 1 to obtain the photocatalytic material (MoS x @Vs-Zn3In2S6-1), denoted as C.

[0050] Comparative Example 1

[0051] A method for preparing a high-efficiency photocatalytic hydrogen production material using a photothermal synergistic pulse deposition method is basically the same as Example 1, except that:

[0052] In step (1), no MoS is added x Precursor co-catalyst (NH4)2MoS4;

[0053] The rest of the operations were the same as in Example 1 to obtain a photocatalytic material (Vs-Zn3In2S6), which was denoted as D.

[0054] like Figure 2 As shown in the UV-visible diffuse reflectance spectra of the photocatalytic materials prepared in Example 1 and Comparative Example 1, MoS x @Vs-Zn3In2S6 is the photocatalytic material prepared in Example 1; Vs-Zn3In2S6 is the photocatalytic material prepared in Comparative Example 1. Figure 2 It can be observed that compared with Comparative Example 1, the absorption wavelength of the material with the addition of a co-catalyst in Example 1 is significantly red-shifted, and the modified material can absorb a wider wavelength, which can improve the visible light absorption efficiency of the semiconductor material, thereby improving the photocatalytic efficiency of the semiconductor material.

[0055] like Figure 3 As shown in the XRD patterns of the photocatalytic materials prepared in Example 1 and Comparative Example 1, MoS x @Vs-Zn3In2S6 is the photocatalytic material prepared in Example 1; Vs-Zn3In2S6 is the photocatalytic material prepared in Comparative Example 1. Figure 3 It can be seen that, in comparison, the position and intensity of the peaks in the photocatalytic composite material prepared by the photothermal synergistic pulse deposition method in Example 1 are basically consistent with those of Vs-Zn3In2S6 in Comparative Example 1, indicating that the addition of MoS x It has no effect on the crystallinity of Vs-Zn3In2S6 and is well distributed on the surface of the Vs-Zn3In2S6 lattice. This may be due to the fact that MoS x The content is small or MoS x The response of Vs-Zn3In2S6 is too weak compared to that of Vs-Zn3In2S6 and therefore not detected in the XRD diffraction. In addition, the intensity and width of the XRD peak of Vs-Zn3In2S6 are similar to those of MoS x Hybridization is irrelevant. This shows that MoS xThe hybrids have little effect on the crystallinity and particle size of Zn3In2S6.

[0056] Comparative Example 2

[0057] Referring to the preparation method in CN103071513B - A hydrogen-producing photocatalyst MoS2 / ZnIn2S4 and its preparation method, a photocatalytic material of 1.2wt% MoS2 / ZnIn2S4 was prepared, denoted as E.

[0058] Experimental Example 1 Testing the performance of photocatalytic materials

[0059] The photocatalytic materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 are coupled to produce hydrogen and convert glucose, and the specific method is as follows:

[0060] 20 mg of photocatalyst (photocatalytic material prepared in Example 1 or Comparative Example 1), 0.3 g of glucose (biomass-glucose is used as a sacrificial agent, and using biomass as a sacrificial agent requires stronger oxidizing ability) and 100 mL of organic solvent (the organic solvent is a mixed solution of acetonitrile and water in a volume ratio of 7:3) are added to a photocatalytic reaction container. The mixture is stirred for 30 minutes before the formal reaction begins to allow the solution to reach adsorption equilibrium. A xenon lamp is used as the experimental light source. The photocatalytic reaction container is in a vacuum state. The generated hydrogen is measured by gas chromatography, and the glucose conversion product is tested by high performance liquid chromatography.

[0061] The method for producing hydrogen using photocatalytic materials in Comparative Example 2 is to add 50 mg of 1.2 wt% MoS2 / ZnIn2S4 into 100 mL of an aqueous solution containing a sacrificial agent (the sacrificial agent acts as a hole consumer) 10.33 g of Na2S and 6.3 g of Na2SO3 to react and collect hydrogen.

[0062] like Figure 4 As shown, the hydrogen production results of the photocatalytic materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1, wherein A is the photocatalytic material prepared in Example 1; B is the photocatalytic material prepared in Example 2; C is the photocatalytic material prepared in the example; D is the photocatalytic material prepared in Comparative Example 1; and E is the photocatalytic material prepared in Comparative Example 2. Figure 4 It can be seen that the photocatalytic material prepared in Comparative Example 1 produces 0.21 mmol / g / h of hydrogen, while the photocatalytic material prepared in Example 1 by the photothermal synergistic pulse deposition method produces 3.63 mmol / g / h of hydrogen, which is 17.3 times that of Comparative Example 1; and the photocatalytic material prepared in Comparative Example 2 produces 3.12 mmol / g / h of hydrogen under the common sacrificial agent system, which is significantly lower than the hydrogen production of the material in Example 1. Therefore, the photocatalytic system described in Example 1 has a high efficiency of hydrogen production. Example 2 reduces the co-catalyst MoS xThe hydrogen production efficiency of the photocatalytic material prepared by the loading amount is 3.02mmol / g / h, which is lower than the hydrogen production efficiency of the photocatalytic material prepared in Example 1, but still has a relatively high hydrogen production efficiency; the hydrogen production efficiency of the photocatalytic material prepared by changing the switching time of the pulsed light deposition in Example 3 is 2.51mmol / g / h. This is because the shortened illumination time leads to a decrease in the degree of photoreduction, which reduces the intensity of the co-catalyst loading and leads to a decrease in the activity of the photocatalytic reaction. The photocatalytic material prepared by changing the loading amount of the co-catalyst and the switching time of the pulsed light deposition still has a relatively high hydrogen production efficiency. Therefore, the photothermal synergistic pulsed deposition method in Example 1 successfully prepared a highly active photocatalytic material.

[0063] like Figure 5 As shown, the glucose conversion product diagram of the photocatalytic material prepared in Example 1, wherein A is the photocatalytic material prepared in Example 1; D is the photocatalytic material prepared in Comparative Example 1. Figure 5 It can be seen that Example 1 can produce 5.04mmol / L of lactic acid and 0.079mmol / L of 5-HMF after 3h of photocatalytic reaction, and Comparative Example 1 can produce 1.85mmol / L of lactic acid and 0.015mmol / L of 5-HMF after 3h of photocatalytic reaction, which provides a new idea for the high-value conversion of biomass. Obviously, the photocatalytic material prepared by the photothermal synergistic pulse deposition method in Example 1 has good hydrogen evolution efficiency and good high-value conversion ability, so the composite photocatalyst of the present invention has efficient photocatalytic activity.

[0064] The results show that the hydrogen production efficiency of the photocatalytic material prepared in Example 1 of the present invention is significantly better than that in Comparative Example 1, and glucose can be converted into other high-value products to a large extent. Compared with Comparative Example 2, the hydrogen production efficiency of Example 1 is also more prominent. In addition, while efficiently producing hydrogen, Example 1 also uses glucose as a "sacrificial agent" to convert glucose into high-value products, thereby achieving high-value conversion of biomass while producing hydrogen.

[0065] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a high-efficiency photocatalytic hydrogen production material using a photothermal synergistic pulse deposition method, characterized in that: The method includes: Vs-Zn3In2S6, (NH4)2MoS4 and alcohol solution were mixed, inert gas was introduced, and the mixture was placed under a xenon lamp light source for photothermal synergistic pulse deposition reaction. The solid was collected by centrifugation, washed, dried and ground to obtain the highly efficient photocatalytic hydrogen production material MoS x @Vs-Zn3In2S6; The photothermal synergistic pulse deposition reaction is carried out under the action of a cyclic switching xenon lamp light source.

2. The method according to claim 1, characterized in that The illumination intensity of the xenon lamp light source is 100 mW / cm 2 The xenon lamp is externally connected to a sunlight simulation filter.

3. The method according to claim 2, characterized in that The cyclic switching xenon lamp means that the time of turning on the lamp each time is 10 to 30 minutes, the time of turning off the lamp each time is 1 to 5 minutes, and the number of times of switching on and off the lamp in cycles is 2 to 5 times.

4. The method according to claim 3, characterized in that The cyclic switching xenon lamp means that the light is turned on for 29 minutes each time, the light is turned off for 1 minute each time, and the number of cycles of switching the light on and off is 3 times.

5. The method according to claim 1, characterized in that The addition ratio of the Vs-Zn3In2S6 and (NH4)2MoS4 is 100 mg: 0.06 mmol.

6. The method according to claim 1, characterized in that The alcohol solution is an ethanol solution or a methanol solution.

7. The method according to claim 6, characterized in that The concentration of the alcohol solution is 10% v / v to 30% v / v.

8. The method according to claim 1, characterized in that The washing is carried out with anhydrous ethanol and deionized water; the drying temperature is 60° C. and the drying time is 12 hours.

9. A high-efficiency photocatalytic hydrogen production material prepared by the method according to any one of claims 1 to 8.

10. Use of the high-efficiency photocatalytic hydrogen production material according to claim 9 in hydrogen production and / or high-value conversion of biomass.

Citation Information

Patent Citations

  • Hydrogen-production photocatalyst MoS2 / ZnIn2S4 and preparation method thereof

    CN103071513B

Cited By

  • Porous photo-thermal catalyst based on reverse confinement induction as well as preparation and application of porous photo-thermal catalyst

    CN120827885A